The Effect of Small Group Discussions on the Knowledge and Attitudes of Female Adolescents Regarding Anemia - Lelly Maria Ervianti; Juda Julia Kristiarini; Atik Ba'diah (Oksitosin : Jurnal Ilmiah Kebidanan, 2026)
Anemia in female adolescents can cause decreased concentration, impaired physical growth, reduced immunity, and lower academic achievement. This research aims to know the effect of small discussion group towards knowledge and attitude of 10th and 11th-grade female students related to anemia at SMAN 6 Pontianak. This is a quantitative research using quasi-experimental design, involving two groups namely experimental group and control group, each consisting of 88 respondents. The sampling technique was carried out using a purposive sampling method, with the research instrument in the form of a questionnaire consisting of 21 knowledge questions and 22 attitude questions. Knowledge scores rose notably in the experimental group after small group discussions (median = 23.83, p = 0.001), with significant improvements in the control group as well (median = 14.29, p = 0.001). Attitude scores increased in both groups (median = 11.00, p = 0.001). Mann–Whitney analysis showed significant post-intervention differences between groups for knowledge (p = 0.001) and attitudes (p = 0.009), indicating that the intervention effectively improved adolescent girls’ knowledge and attitudes toward anemia. Small group discussions have been proven to be effective in improving the knowledge and attitudes of female adolescents regarding anemia.